Material properties of ex-vivo milk chocolate boluses examined in relation to texture perception - Qi, He; Bramante, Filippo; Davies, Andrew; Elleman, Carole; Fourtouni, Kelly; Wolf, Bettina (Royal Society Of Chemistry, 2018)
The texture perception of chocolate products is a major driver for consumer liking and the popularity of this confectionary category. Whilst some texture attributes are clearly linked to the material properties of the chocolate bar itself, others are closer related to the properties of the chocolate bolus. However, little is known around the material properties of chocolate boluses. Hence the aim of this study was to gain more in-depth insights into this area and to evaluate how chocolate bolus material properties link to texture and mouthfeel perception. Boluses prepared from four milk chocolates were analysed for microstructure, particle size, and composition and friction properties. The boluses showed the expected oil-in-water emulsion microstructure. The emulsion droplets were composed of fat and milk protein with clear evidence for presence of milk protein not only at the droplet interface but also in the droplet bulk phase. The type of adsorbed milk protein depended on the presence or absence of interfacially adsorbed cocoa solids, grouping the four chocolates into two pairs. The chocolate boluses showed increased friction compared to saliva and at low sliding speed the friction coefficients were lower for boluses with interfacially adsorbed cocoa solids. Perceived differences in mouthcoating were reflected in the mixed regime of the Stribeck curve. Thickness perception on the other hand was reflected in the hydrodynamic regime of the friction curves. This research has highlighted promise in analysing material properties of chocolate boluses in view to understanding perceived texture.